Understanding 4-H Youth Development Delivery - Marilyn N. Norman; Joy C. Jordan (EDIS, 2006)
4-H uses a variety of methods and locations for reaching youth with opportunities that help them grow and develop in positive ways. This document is 4-HS FS101.5, one of a series of the Florida 4-H Program, UF/IFAS Extension. Published May 2006.